Application of crushed rice flour in food technology - Z. M. Kunasheva; M. K. Kodzokova (Новые технологии, 2018)
The article considers the features of crushed rice flour and its effect on the quality indicators of finished bakery products in various methods of dough preparation and dosages. The dependence of the acidity level of the crumb on the acidity level of a semi-finished product made from crushed rice flour and the dependence of the duration of fermentation of rice ferment on its dosage have been investigated. Methods for the study of quality indicators of finished products have been studied.